Vukovar: The case of an ethnically divided city - Čorkalo, Dinka (2003)
Post-war processes in many communities illustrate the impact that war had on people who used to live together, the intensity of mutual transgressions, the extent of the mistrust among conflicting groups and the difficulties of the renewal of the social life after the war. We discuss two examples of cities that are deeply divided along the ethnic lines. In Mostar this division has been facilitated by the fact that the city is located on the banks of the river Neretva, where the east coast is populated mainly by Moslems, and the west bank by Croats. In Vukovar there is no such a physical separation, however this city is a proof that the existence of physical boundaries is not a necessary condition for the creation of the psychological wall: Croats and Serbs in Vukovar live in physically unified city, however, as it will be seen, it is a city with a social geography heavily marked by ethnicity. We commented examples of such marking and their implication for organizing social life in the community. We also discuss possible ways for overcoming ethnic boundaries in divided communities.